Audio Message Complexity: Audio Content Change (Acc) and Audio Information Introduced (Aii) - Potter, Robert F.; Lang, Annie (The Sourcebook of Listening Research: Methodology and Measures, 2017)
Two measures are used in combination to provide a human‐centered measure of audio message complexity. The first measure—Audio Content Change (Acc)—counts how many times specific auditory structural features occur during the presentation of a message. Because these structural features are known to elicit orienting responses in listeners, Acc is conceptualized as quantifying the relative amount of cognitive resources automatically allocated to the message. The second measure—Audio Information Introduced (Aii)—results from listening to the audio immediately following each Acc and determining the relative amount of cognitive resources required to process the novelty and motivational relevance of the sounds heard. Although fairly new measures, initial results suggest that Acc and Aii provide valid measures of the auditory complexity of messages globally as well as at local levels of specific auditory change.